The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1143/jjap.39.6136
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Transient Enhanced Diffusion in B+-Implanted Si by Buried Boron Isotopes

Abstract: A method was developed to investigate the transient enhanced diffusion (TED) of implanted boron by observing the redistribution of buried boron isotopes in the implanted region. The buried layer was created by 10B+ implantation and the implant damage was induced by 11B+ implants at various doses. With low-dose ion implantation, implanted dopants exhibit similar TED behavior as embedded dopants. For implant doses higher than 5×1014 cm-2, the uphill diffusion of 10B near the immobile 11B peak indicates the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…9,13,[42][43][44][45] In some cases, pile-up has been observed in the vicinity of a surface or interface, 9,42,44 sometimes within 1 nm of the surface. Such peaks impose a severe test of secondary-ion-mass spectroscopy ͑SIMS͒.…”
Section: B Dopant Pile-upmentioning
confidence: 99%
“…9,13,[42][43][44][45] In some cases, pile-up has been observed in the vicinity of a surface or interface, 9,42,44 sometimes within 1 nm of the surface. Such peaks impose a severe test of secondary-ion-mass spectroscopy ͑SIMS͒.…”
Section: B Dopant Pile-upmentioning
confidence: 99%
“…Previous research has demonstrated that the diffusion behavior of 10 B is similar to that of 11 B when both are implanted at a dose of 5 Â 10 13 cm À2 . 8) The density of residual dislocation loops was monitored by planview transmission electron microscopy (TEM).…”
Section: Methodsmentioning
confidence: 99%
“…An approach has been developed to observe the diffusion in the peak region of B þ implantation profiles by using an embedded layer of boron isotopes. 8) This work employs this method to analyze boron reactions near the peak region of the boron profiles during annealing following the high-dose implantations of B þ and BF 2 þ . The two implantation species exhibit different TED behaviors and boron clustering upon annealing at 750 C.…”
Section: Introductionmentioning
confidence: 99%